The Impact of the Reality Show “Clash of Champions” on the Learning Motivation of International Special Class Students (KKI) FTIK UINSI Samarinda - Muhammad Nurhadi Setyawan; Shafa Shafa; Atika Muliyandari (Jurnal Tarbiyah dan Ilmu Keguruan Borneo, 2025)
This research is motivated by the rapid development of digital media that indirectly affects the world of education, especially through platforms such as YouTube. One of the educational shows that attracts attention is the Clash of Champions reality show produced by Ruangguru. This reality show carries the concept of competition between outstanding students from various well-known campuses, which is packaged in an inspiring and entertaining format. This type of show is relatively new and rare, but it has managed to attract the interest of many students, including university students. This reality show not only presents intellectual competition, but also emphasizes values such as the spirit of learning, teamwork, and perseverance. Thus, the purpose of this study is to determine the impact of the reality show “clash of champions” on the motivation of students of the International Special Class (KKI) FTIK UINSI Samarinda" in increasing learning motivation. This research uses a qualitative descriptive approach. The source of the data comes from International Special Class (KKI) students of the Faculty of Education and Teacher Training, UIN Sultan Aji Muhammad Idris Samarinda batch 7, 8, and 9. The techniques used to collect data are observation and interviews. The results show that the reality show “Clash of Champions” exhibits a complex dual impact on students' learning motivation. While positively inspiring increased motivation to study, discipline, consistency, resilience, as well as encouragement to explore potential and design life goals, the program also has a negative impact. The motivation generated tends to be momentary and uneven, with criticism of its excessive entertainment focus, potential mental stress, evil editing, unequal access to education, and function as a promotional medium. This confirms that its effectiveness in creating a persistent, inclusive, deep and ethical learning drive remains a challenge.